La presencia de una familia neotropical (Malpighiaceae) en el extremo más austral Sudamérica en el Eoceno - Fernández, Damián Andrés; Panti, Carolina; Palazzesi, Luis; Barreda, Viviana Dora
Presented here is the discovery of pollen grains and a foliar impression assigned to Malpighiaceae from the Río Turbio Formation, SW Santa Cruz Province, indicating the presence of this Neotropical family in the southernmost tip of South America by the Eocene. Perisyncolporites pokornyi Germeraad, Hopping & Muller, erected to group fossil pollen similar to Malpighiaceae, includes a wide variety of pollen-forms with a complex aperture distribution, more or less concordant with the sides of a hexagon. The extant clades most closely related to the fossil forms of the Río Turbio Formation (Tetrapteroids and Stigmaphylloids) are today distributed in tropical and subtropical regions of South America, reaching up to the 35ºS. The only extant species distributed closer to the studied area, and that, in turn, represents the world’s southernmost penetration of the family (Gallardoa fischeri Hicken, reaching the 42°S), is morphologically unrelated to the studied fossils. The foliar impression is similar to those recognized previously in the Río Pichileufú locality, Río Negro Province (Mascagnia sepiumoides Berry, Tetrapteris precrebrifolia Berry), and also in the Río Turbio Formation (Tetrapteris precrebrifolia Berry). The present results support earlier hypotheses that suggest a major penetration of Neotropical lineages into the southernmost latitudes during the Eocene as well as a possible migration to Australia via Antarctica, at least of those perisyncolporate-related forms. Fil: Fernández, Damián Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Panti, Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Palazzesi, Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación ...